Highly sensitive, tunable, and durable gold nanosheet strain sensors for human motion detection. Issue 24 (25th May 2016) - Lim, Guh-Hwan; Lee, Nae-Eung; Lim, Byungkwon
Abstract : We report highly sensitive, tunable, and durable strain sensors based on a simple structure consisting of a multilayered film of gold (Au) nanosheets as a sensing layer on a highly stretchable Ecoflex substrate. Abstract : We report highly sensitive, tunable, and durable strain sensors based on a simple structure consisting of a multilayered film of gold (Au) nanosheets as a sensing layer on a highly stretchable Ecoflex substrate. The high sensitivity of the sensor at different levels of strain was achieved by controlling the stacking number of micrometer-sized Au nanosheets with a thickness of ∼20 nm, which enabled the control of piezoresisitivity of the sensing layer through the change in contact resistance between Au nanosheets under mechanical bending and stretching. The Au nanosheet-based strain sensors exhibited excellent electrical stability without degradation in sensing-performance even after 10 000 stretching cycles. Our highly sensitive, reproducible, tunable, and durable strain sensors were demonstrated to monitor large-scale body motions such as bending, walking, jumping, and squatting, as well as to detect small skin strains induced by minute movements of muscles upon breathing, speaking, and coughing.